Australasian Diabetes Data Network: Building a Collaborative Resource. (September 2016) - Clapin, Helen; Phelan, Helen; Bruns, Loren; Sinnott, Richard; Colman, Peter; Craig, Maria; Jones, Timothy; ,
Australasia is a region with a high incidence of type 1 diabetes (T1D). There are approximately 140 000 individuals with T1D, and of these 10 000 are children. Although the region covers a huge geographical area, most children with T1D are managed by tertiary academic centers in the major capital cities. Local longitudinal data collection has been in place for several decades in most of these centers, however ongoing national data collection had not been attempted. In 2012, with funding from the Juvenile Diabetes Research Foundation (JDRF) Australian Type 1 Clinical Research Network, a national collaboration was formed to provide ongoing longitudinal collection of T1D patient characteristics and outcomes. The initial phase of this collaboration, known as the Australasian Diabetes Data Network or ADDN, was led by the Australasian Paediatric Endocrine Group (APEG) and thus included only children and adolescents. The next phase, commenced in 2016, will see adult sites added through collaboration with the Australian Diabetes Society (ADS). As most of the initial centers had longitudinal data collection in place the model employed was to establish the transfer and collation of data already collected into a central database. This required the definition of a common data dictionary, ethics and governance procedures and the employment of technology to enable efficient and accurate information transfer and accessibility. The ADDN project received widespread support from the diabetes research community with study investigators representing 20 pediatric centers across the region. The first phase focused on the 5 largest centers and at the end of 2015 these centers were uploading patient data to the ADDN database on a quarterly basis resulting in 5271 patients with 83 506 diabetes visits.